SELECTION MODEL FOR 9 METERS HANDBALL PLAYERS - JUNIOR 2 - Chiruț Adrian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Backcourt players and center players cover larger distances and spend less time standing and walking. In the handball game, the optimal period for performance is 16-18 years, therefore, training for specialized positions starts at a young age. The aim of this research was to determinate the somatic and technical characteristics of young handball players that belong to University Sport Club Of Suceava (backcourts and centers players). Backcourt and centers players have a very important role in the team and their selection and preparation had to be done carefully. The results obtained from the measurement of players on the positions of backcourts and centers have shown that there are players in the junior team II with special somatic, motor and technical possibilities and suitable to obtain multiple performances in the future.